Discovery of substituted-2, 4-dimethyl-(naphthalene-4-carbonyl)amino-benzoic acid as potent and selective EP4 antagonists. Issue 1 (1st January 2016) - Blanco, Maria-Jesus; Vetman, Tatiana; Chandrasekhar, Srinivasan; Fisher, Matthew J.; Harvey, Anita; Mudra, Daniel; Wang, Xu-Shan; Yu, Xiao-Peng; Schiffler, Matthew A.; Warshawsky, Alan M.
Graphical abstract: Abstract: A novel series of EP4 antagonists, based on a quinoline scaffold, has been discovered. Medicinal chemistry efforts to optimize the potency of the initial hit are described. A highly potent compound in a clinically relevant human whole blood assay was identified. Selectivity and pharmacokinetic profiles of this compound are discussed.